Contemporary Ulama Critiques on the Application of Letters of Credit in Modern Trade Finance - Nur Hidayati; Asmawi; Nur Hidayah; Satriya Nugraha; Syariful Anam; Ahmad Alsharu (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
This article examines contemporary Islamic scholars' criticisms of the conventional letter of credit (LC) structure, particularly the documentary compliance principle embodied in Article 14 of the Uniform Customs and Practice for documentary credits (UCP 600). While LC has long functioned as a central payment mechanism in international trade, its document-based structure has raised normative concerns among contemporary scholars of Islamic finance. This study aims to analyze the structural features of Article 14 UCP 600, classify the main strands of scholarly criticism, and assess their empirical relevance through judicial decisions involving LC disputes. The research adopts a qualitative socio-legal approach that combines normative analysis of contemporary scholarly literature with empirical examination of court decisions. The normative data comprise international LC standards and scholarly works on autonomy, ownership, contractual structure, and uncertainty in LC transactions. Empirical data are drawn from Indonesian court decisions involving LC disputes between 2019 and 2025, identified through the Supreme Court's decision directory. A Total of nine cases explicitly related to LC were analyzed using descriptive statistical mapping and qualitative legal analysis. The findings reveal three structural patterns in LC disputes. First, most conflicts are centered on documentary compliance and payment obligations rather than the underlying goods, confirming the formalistic nature of LC disputes. Second, more than half of the contractual framework of LC-based financing. Third, a significant proportion of criminal cases demonstrates the risk of fraudulent or fictitious transactions enabled by the document-based system. The empirical patterns closely align with contemporary scholarly critiques, which highlight the structural separation between documents and real transactions, contractual ambiguity, and the potential for uncertainty. The study concludes that the documentary structure of conventional LC lacks the practical relevance of contemporary scholarly criticisms. This study contributes to strengthening contemporary Islamic finance scholarship by demonstrating the empirical relevance of Islamic scholarly critiques of the documentary structure of the conventional Letter of Credit under Article 14 of UCP 600 in modern trade finance disputes.